An Overview on Water Quality Trending for Lake Water Classification in Malaysia - Muzzammil Shahabudin, Muhammad; Musa, Sabariah (International Journal of Engineering and Technology, 2018)
Lake water is important to all life and surroundings with multiples benefits and forms either in natural or man-made conditions. One of the most well-known tools for assessing the water quality is Water Quality Index (WQI) and widely used including Malaysia. Lake water quality should be represented in lucid way like other surface water regarding to the WQI standards for water quality assessment on lakes. This paper aims to review on lake water quality classification and its uses based on WQI standards in Malaysia. In this review, the uses of WQI for assessing the lake water and functioned of lakes are discussed. Results on pH from 5.0 to 9.2, BOD in mg/l from 0 to 180, COD in mg/l from 5 to 150, SS in mg/l from o to 1800, DO in mg/l from 0 to 8 and AN in mg/l N from -1 to 26. Variety of numbers is due to different loading of pollutions and location. With used of WQI on lake water quality assessments, further action can be taken for the uses on water resources by maintaining the quality. It also will broaden the uses of lake water as alternative of water resources in Malaysia.Â Â